ПРИНЦИПЫ И ПУТИ РАЗВИТИЯ ПРОФЕССИОНАЛЬНОЙ КОМПЕТЕНТНОСТИ ПРЕПОДАВАТЕЛЯ ИНОСТРАННЫХ ЯЗЫКОВ В СООТВЕТСТВИИ С ГОС РУЗ - Рашидова, Ф.М. (SCIENCE and SOCIETY, 2017)
In the article the author shows the importance of continuous professional development(CPD) of the teachers of foreign languages in learning, teaching and assessment under the concept of the CEFR. The recommendations of the CEFR were accepted as basic concept of cardinally new state standard for the whole education system of Uzbekistan. It also describes the ways and principels on developing the teacher’s personal and professional skills in order to realize the requirements of the State Standard, including some methodology.
Keywords: CEFR; CPD; methodology; system of assessment; TOEFL; IELTS; State Standard; principels; quality assurance of the education